Transactional capability: Innovation's missing link - Jorge Tello-Gamarra; Paulo Antônio Zawislak (Journal of Economics, Finance and Administrative Science, 2013)
The topic of innovation as a source of competitive advantage for firms is consolidated in the literature. An innovation-based advantage is generally achieved by following a structured process, in which technological capability plays a key role. However, a question remains in studies into innovation, which is concerned with the reasons why not all firms that develop a technological capability are innovative. Where is the missing link? Great efforts have been made in attempts to answer to this question. However, the study of this link as a source of advantage for firms deserves further attention. This article aims to present a framework with two essential dimensions: (1) the technological capability and (2) the transactional capability. Technological capability is the ability of firms to make effective use of technical knowledge in order to improve production processes and develop new products and services. Transactional capability is defined as a repertoire of abilities, processes, experiences, skills, knowledge and routines that the firm uses to minimize its transaction costs (ex-ante and ex-post). Given that the present study is a theoretical paper, methodologically it is based on a literature review. The main finding of this study is the identification of transactional capability as the missing link in innovation. Accordingly, to be innovative, in addition to having a technological capability, a firm needs to develop its transactional capability. – – La innovación como fuente de ventaja competitiva de la firma es un tema consolidado en la literatura. Una ventaja basada en la innovación se alcanza, generalmente, a través de un proceso estructurado, donde la capacidad tecnológica tiene un papel crucial. No obstante, una cuestión que continúa pendiente en esta área de investigación es la de identificar por qué no todas las firmas que desarrollan su capacidad tecnológica son innovadoras. Dónde está el eslabón perdido? Muchos esfuerzos ya fueron realizados para tratar de responder a esa pregunta. Sin embargo, el estudio de este eslabón perdido, como fuente de ventaja para la firma merece más atención. El presente artículo tiene por objeto presentar un framework con dos dimensiones esenciales: (1) la capacidad tecnológica y (2) la capacidad transaccional. La capacidad tecnológica es la habilidad que tiene la firma para hacer uso efectivo del conocimiento técnico para mejorar los procesos productivos y desarrollar nuevos productos y servicios. La capacidad transaccional es definida como un repertorio de habilidades, procesos, experiencias, destrezas, conocimiento y rutinas que la firma usa para minimizar sus costos de transacción (ex-ante y ex-post). Dado que este estudio se caracteriza como un artículo teórico, metodológicamente está basado en una revisión bibliográfica. El hallazgo principal de este estudio es la identificación de la capacidad transaccional como el eslabón perdido de la innovación. En este sentido, para que una firma sea innovadora debe, además de tener capacidad tecnológica, desarrollar su capacidad transaccional.
Keywords: D23; K00; 330; The firm; Technological capability; Transactional capability; Innovation; Firma; Capacidad tecnológica; Capacidad transaccional; Innovación